Sexual health promotion interventions in Iranian postmenopausal women: A systematic review of randomized controlled trials - Maryam Masoumi; Afsaneh Keramat; Maryam Farjamfar; Seyedeh Solmaz Talebi (Wolters Kluwer Medknow Publications, 2024)
This study aimed to systematically review published articles on sexual health promotion interventions in postmenopausal Iranian women. Five databases including PubMed, ProQuest, Web of Science, Science Direct, and Google Scholar, as well as three Iranian databases, including SID, IranDoc, and Magiran, were searched without a time limit for sexual health promotion interventions in Iranian postmenopausal women. The risk of bias was assessed using the Jadad scale. In total, 48 articles met our inclusion criteria and provided data for this review. The measured outcomes were different aspects of sexual function. Outcomes were measured using a specific questionnaire related to sexual function and its areas. The results obtained from the tools used have led to the classification of the results based on the type of interventions used to improve the sexual health of postmenopausal women. The main groups were drug interventions (chemical and herbal) and non-drug interventions (psychological and educational). Surveys showed that most interventions performed on sexual health in Iranian postmenopausal women were medicinal (herbal) interventions. Numerous studies obtained a good quality score. The results of this study can be used to improve the sexual health of postmenopausal women.